362 Trends in the use/non-use of guideline-directed medical therapy in non-ischaemic dilated cardiomyopathy with improved ejection fraction. (8th December 2021) - Santi, Giovanni; Manca, Paolo; Nuzzi, Vincenzo; Venturelli, Francesco; Ramani, Federica; Barbati, Giulia; Gregorio, Caterina; Stolfo, Davide; Merlo, Marco; Sinagra, Gianfranco
Abstract: Aims: Guideline-directed medical therapy (GDMT) is associated with significant improvement of left ventricular function in an important fraction of patients with non-ischaemic dilated cardiomyopathy (NICM), and the recent definition of heart failure with improved ejection fraction (HFimpEF) highlights the importance of longitudinal assessment of left ventricular ejection fraction (LVEF); however, little is known about the long-term outcome of GDMT downtitration in patients with NICM who develop HFimpEF. We sought to assess the functional and prognostic impact of GDMT downtitration in this subgroup. Methods and results: All consecutive NICM patients enrolled from 1991 to 2018 in the Trieste Heart Muscle Disease Registry with baseline LVEF ≤40% and with ≥1 LVEF assessment after baseline were included. ImpEF was defined as a baseline LVEF ≤40%, a ≥ 10 point increase from baseline LVEF, and a second measurement of LVEF >40%. GDMT downtitration was defined as any dose reduction or drug withdrawal of renin-angiotensin system inhibitors (RASi) or beta-blockers (BB). The outcome measures were a loss of impEF criteria, a composite of all-cause death and heart transplantation (ACD/HTx), a composite of HF hospitalization, heart transplantation and left ventricular assist device (HFH/HTx/LVAD), and a composite of sudden death and major ventricular arrhythmias (SD/MVA). The prognostic role of GDMT downtitration was assessed with Kaplan–Meier analysis and curves of cumulative incidence, considering GDMT downtitration, loss of impEF, and the composites of outcome as time-dependent variables. Among 452 NICM patients with impEF, 186 (41.2%) downtitrated GDMT (median time to downtitration 35 months). Loss of impEF criteria occurred in 186 patients (median time to loss of impEF 51 months). While no significant differences in terms of ACD/HTx, HFH/HTx/LVAD, or SD/MVA among those who downtitrated GDMT and those who didn't were observed, the population that downtitrated GDMT had a higher cumulative incidence of loss of impEF ( P < 0.001). Conclusions: In NICM patients who develop impEF, we observed a ≈ 40% rate of recurrent decline of LVEF. GDMT downtitration seems to be associated with this functional deterioration, although no differences in terms of major cardiovascular outcomes emerged.